La acción de protección como una garantía constitucional de aplicación directa vulnerada por la ley orgánica de garantías jurisdiccionales y control constitucional - Cordova Mashiant, Romel Bladimir (2016)
This research was motivated because principles are established in the Constitution of the Republic of Ecuador governing compliance with the standard and between we find the principle of direct application of protective action as a mechanism for effective protection of rights violated by any administrative decision of a judicial authority or not, this is one of the fundamental rights that protects persons who are intended to violate any law, a mechanism is established in Article No. 88 of the Constitution of the Republic of Ecuador , source and guarantee established throughout the social sector, and in relation to the subject we mean the general public, whether it individually or collectively; we mean that this law is in complete contradiction to the aforementioned legal provision, so that in the Organic Law of Judicial Guarantees and Constitutional Control in Article 40 No. 3 the principle of direct and effective implementation of rights is violated guaranteed in our Constitution, thus creating the need for a thorough study of this contradiction violation of rights or guarantees, this paramount virtue that generates damage to the spirit of the rule itself. While the Constitution of the Republic of Ecuador is the supreme law and therefore hierarchically superior to any other law that endorses it, more so in this research we found that the Organic Law of Judicial Guarantees and Constitutional Control limits constitutional rights; so it is imperative the need for reform of Article 40 No. 3 of the Organic Law of Judicial Guarantees and Constitutional Control, as the Constitution provides a clear way that the existence of the violation of a constitutional right is only necessary to apply protective action in a direct and effective manner. The action of protection is a new mechanism, this was implemented in the 2008 Constitution, based on this we can determine that this legal no subsidiarity attached to it with respect to the Organic Law of Judicial Guarantees and Constitutional Control, which clearly the contradiction of a clearly established and precise, well if work is focused on this fundamental issue. At present this incongruity between the Organic Law of Judicial Guarantees and Constitutional Control and the Constitution of the Republic of Ecuador has become so notorious and is therefore the authorities of the Ecuadorian state should study the minutiae of law, respect guarantees this right or will make in an orderly sequence strengthen and implement other right both individual and thus generate that balanced work environment, with protection of the rights and guarantees subject to a rule that does not infringe any constitutional principle.